2020
DOI: 10.3390/vaccines8040686
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perception of Healthcare Workers Concerning Influenza Vaccination during the 2019/2020 Season: A Survey of Sicilian University Hospitals

Abstract: Influenza is an infectious disease with a high impact on the population in terms of morbidity and mortality, but despite International and European guidelines, vaccination coverage rates among healthcare workers (HCWs) remain very low. The aim of the present study was to evaluate influenza vaccination adherence in the three Sicilian University Hospitals of Catania, Messina, and Palermo and to understand the attitudes and perceptions of vaccinated healthcare workers and the main reasons for vaccination refusal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…All HCP must be skilled in occupational exposure risks and preventive and protective procedures. Furthermore, previous studies in the same Italian hospital have shown their low vaccination coverage for VPDs [ 9 , 22 , 23 , 24 , 26 , 28 ]. This exposes themselves and their patients to VPDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All HCP must be skilled in occupational exposure risks and preventive and protective procedures. Furthermore, previous studies in the same Italian hospital have shown their low vaccination coverage for VPDs [ 9 , 22 , 23 , 24 , 26 , 28 ]. This exposes themselves and their patients to VPDs.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks due to VPDs continue to occur in various healthcare settings globally, threatening patients, HCP, and healthcare services [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Indeed, compliance with recommendations for vaccination among HCP is often suboptimal [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Consequently, to sustain vaccine-acquired herd immunity and vaccination policies, the immunization coverage of the HCP must reach the fixed threshold rates [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows a slightly higher willingness to vaccinate (77%) which could be explained by the greater presence of medical students in our sample, who are more willing to vaccinate. In this context, the risk perception may increase the willingness to get vaccinated, especially in medical students, as a higher self-perceived risk of contracting influenza is associated with better adherence to flu vaccination [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the fear of potential damages after receiving the vaccine raises concern among people possibly leading to a reduction in the vaccine uptake [9]. In addition, self-perceived risk (both of influenza and COVID-19) may impact the willingness to get vaccinated [10]. Although the attitudes towards a future vaccine to prevent COVID-19 have been already investigated in the general and young population [11,12], evidence on the impact of COVID-19 pandemic on flu vaccination intentions in the young population is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Responsibility for public health messaging primarily lies with governments, scientists and medical professionals [31][32][33].…”
Section: Discussionmentioning
confidence: 99%